THE QUANTITY AND QUALITY OF OBSERVATIONAL NIGHTS MONITORED WITH USING THE ASTRONOMICAL INSTRUMENTS AT THE SUBURBAN OBSERVATION STATIONS OF ASTRONOMICAL OBSERVATORY OF ODESSA NATIONAL UNIVERSITY - Kashuba, S. G.; Gorbanev, Yu. M.; Andrievsky, S. M.; Marsakova, V. I.; Troianskyi, V. V. (Одеські астрономічні публікації, 2016)
The Astronomical Observatory of Odessa National University named after I.I. Mechnikov is one of the four astronomical observatories which exist in classical universities. The Observatory has a main office in the T.G. Shevchenko Park that located near historical center of Odessa. The Observatory also has several observation stations: in the Odessa suburb Mayaki and Kryzhanovka villages.